The Development of Uzbek Banks and Their Place in A Market Economy - Ganieva Umida Abdugaffarovna (Genius Journals, 2022)
This article provides an overview of the nature of banks, their origins and their role in a market economy
Keywords: investors; infrastructure; negative impact